2009
DOI: 10.1051/forest/2009047
|View full text |Cite
|
Sign up to set email alerts
|

Sélection très précoce pour les propriétés du bois massif : détection précoce des individus les plus performants

Abstract: Abstract• This article reviews the theoretical basis for indirect selection -where early selection is an example -and how correlated response is calculated.• The review is followed by a description of issues as to the choice of selection criteria that could explain the lack of substantial progress on breeding for wood quality. These include: the autoregressive nature of selection criteria, overemphasizing the importance of basic density as selection criterion, ignoring age-related trends of wood properties, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 34 publications
(33 reference statements)
1
33
0
2
Order By: Relevance
“…Therefore, improved wood density trait is expected to meet a wide range of demands and potential for future utilization. Current studies [9][10][11][12][13] have indicated that wood density, with high heritability and large economic gain from selection, is an ideal selection criterion for tree breeding programmes because of its strong effect on wood quality. Heritability of wood density is generally found to be higher than those of growth traits in forest trees.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improved wood density trait is expected to meet a wide range of demands and potential for future utilization. Current studies [9][10][11][12][13] have indicated that wood density, with high heritability and large economic gain from selection, is an ideal selection criterion for tree breeding programmes because of its strong effect on wood quality. Heritability of wood density is generally found to be higher than those of growth traits in forest trees.…”
Section: Introductionmentioning
confidence: 99%
“…Studies which have used acoustics to obtain stiffness measurements on juvenile trees include references. 12,44,143,144,160,177,213,[256][257][258][259][260][261][262][263][264][265][266][267] Many of these have investigated the effect of stress such as tilting or drought. Investigations using acoustic velocity for more mature juvenile trees include references.…”
mentioning
confidence: 99%
“…McKimmy and King (1980) find that early selection of high density trees can improve mature tree density. Wu et al (2007) and Apiolaza (2009) use this early selection criterion for screening the best individuals for wood quality.…”
Section: Discussionmentioning
confidence: 99%